The first Brazilian Field Lab fully dedicated to CO2 MMV experiments: From the start-up to the initial results - De Castro Araujo Moreira, Andréa Cristina; Musse, Ana Paula Santana; Do Rosário, Fátima; Lazzarin, Helen Simone Chiaranda; Cavelhão, Gabriel; Chang, Hung Kiang [UNESP]; Oliva, Andresa [UNESP]; Landulfo, Eduardo; Nakaema, Walter Morinobu; Melo, Clarissa Lovato; Bressan, Lia Weigert; Ketzer, João Marcelo; et al. (Elsevier, 2014)
Currently one of the main challenges in CO2 storage research is the development, testing and validation of accurate and efficient Measuring, Monitoring and Verification (MMV) techniques to be deployed at geological sequestration sites that are cost effective yet help minimize risk. This perspective motivated PETROBRAS, the National Oil Major in Brazil, through its R&D investments portfolio to prioritize research projects that would contribute to decreasing the technological gap in the area. The Company's periodic surveys indicated the lack of infrastructure, as well as expertise in CO2 MMV, as two of the most critical issues at the national level. In order to bridge that gap, initial steps were taken in 2010 for the start-up and development of the first CO2 MMV Field Lab in Brazil, fully sponsored by PETROBRAS, with a long term goal of enabling the ranking of the best, most costeffective MMV technology alternatives to be deployed at commercial large scale CCGS sites scheduled to be installed in the country. In addition to providing basic infrastructure to carry out the CO2 injection and controlled release experiments, the facility was designed for the simultaneous testing of multiple measuring methodologies. Additional benefits of the initiative are the creation of expertise and the acceleration of the know-how in MMV in Brazil, as well as the development of a deeper and more practical knowledge of CO2 dynamics and impacts in a real world, open air scenario. Under the full support of the PETROBRAS R&D Center (CENPES), through its Climate Change Mitigation Technological Program (PROCLIMA), the Brazilian Pilot CO2 MMV Lab was made possible through a joint 4-year research Project, conceived and carried out by PETROBRAS and local academia in Brazil, in close cooperation with international experts. An overview of the Project and the multiple research areas encompassed will be presented, together with the preliminary results of the first CO2 injection campaign, which took place in 2013.
Keywords: Carbon dioxide atmospheric detection; Carbon dioxide controlled release; Carbon dioxide flux; Carbon dioxide monitoring; Eddy covariance; Geological carbon sequestration; Geophysical monitoring; Near surface monitoring